2021
DOI: 10.4103/aian.aian_627_19
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Oligodendrocyte Glycoprotein (MOG)-IgG Associated Demyelinating Disease

Abstract: Background: Discovery of serum myelin oligodendrocyte glycoprotein (MOG) antibody testing in demyelination segregated MOG-IgG disease from AQ-4-IgG positive NMOSD. Aims: To study clinico-radiological manifestations, pattern of laboratory and electrophysiological investigations and response to treatment through follow up in MOG-IgG positive patients. Method: Retrospective data of MOG-IgG positive patients was collected. Demographics, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…[ 21 22 25 26 27 ] The larger studies of MOG antibody disease reported a high incidence in paediatric age group and no gender bias, similar to our study. [ 21 22 25 26 27 ] Preceding clinical events were more frequent in MOG positive group while number of patients with relapse were similar in both the groups.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[ 21 22 25 26 27 ] The larger studies of MOG antibody disease reported a high incidence in paediatric age group and no gender bias, similar to our study. [ 21 22 25 26 27 ] Preceding clinical events were more frequent in MOG positive group while number of patients with relapse were similar in both the groups.…”
Section: Discussionsupporting
confidence: 87%
“…However, in the previous larger studies ON was found to be more common than myelitis. [ 21 22 25 26 27 ] The spinal cord involvement in all myelitis cases in both the groups of our study was in the form of LETM and we did not find any short segment spinal cord lesions.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…From Western India, 4 out of 31 MOGAD patients were shifted to rituximab therapy in view of severe disease. [ 25 ] The mean ARR reduced from 1.08 to 0.43 on rituximab with no further relapses on follow up. [ 25 ] In the present study, 4 MOGAD patients received rituximab as a second or third-line agent.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] The mean ARR reduced from 1.08 to 0.43 on rituximab with no further relapses on follow up. [ 25 ] In the present study, 4 MOGAD patients received rituximab as a second or third-line agent. As mentioned earlier, 2 of them were free of relapses over a period of 2.5 years after initiation of therapy.…”
Section: Discussionmentioning
confidence: 99%